Remote empyemas in mediastinum as a complication of dental gangrene – case report - Rafałko, Tomasz; Dudzińska-Filkiewicz, Anna; Żurada, Anna; Batia, Anna (Journal of Stomatology, 2017)
Abstract Background: submandibular abscesses often appear as a consequence of negligence in maintaining hygiene and oral health, however, sometimes as a result of the lack of anatomical obstacles in this body area, inflamatory processes can easily spread to neighboring space, as well as locally distant ones, reaching even the mediastinum. Case report: a 26-year-old woman without a clinically relevant history was admitted to the Maxillofacial Surgery Department because of an abscess involving the submandibular and parapharyngeal space on the left side. Probably, in the beginning the submandibular abscess, reached subsequently the parapharyngeal space, turning into the neck phlegmon with the fulminant clinical course despite appropriate treatment. Eventually, the submandibular abscess covered the neck space and moved to the mediastinum where the empyemas were created, therefore the lifesaving thoraic surgery was needed. Conclussion: only conscious profilaxis and pro-health attitude of the patients can help to reduce the number of people treated due to the odontogenic circumaxillary and paramandibular infections and their complications that in specific cases, can be a direct thread to life, even among young and healthy patients. Dentists and other physicians should be alerted about how serious general complications, directly threatening patient’s life, can occur in a situation of untreated primary infection outbreaks, generally considered to be trivial.